PMTCT Option B+ Does Not Increase Preterm Birth Risk and May Prevent Extreme Prematurity: A Retrospective Cohort Study in Malawi. (1st April 2017) - Chagomerana, Maganizo B.; Miller, William C.; Pence, Brian W.; Hosseinipour, Mina C.; Hoffman, Irving F.; Flick, Robert J.; Tweya, Hannock; Mumba, Soyapi; Chimbwandira, Frank; Powers, Kimberly A.
Abstract : Objective: To estimate preterm birth risk among infants of HIV-infected women in Lilongwe, Malawi, according to maternal antiretroviral therapy (ART) status and initiation time under Option B+. Design: A retrospective cohort study of HIV-infected women delivering at ≥27 weeks of gestation, April 2012 to November 2015. Among women on ART at delivery, we restricted our analysis to those who initiated ART before 27 weeks of gestation. Methods: We defined preterm birth as a singleton live birth at ≥27 and <37 weeks of gestation, with births at <32 weeks classified as extremely to very preterm. We used log-binomial models to estimate risk ratios and 95% confidence intervals for the association between ART and preterm birth. Results: Among 3074 women included in our analyses, 731 preterm deliveries were observed (24%). Overall preterm birth risk was similar in women who had initiated ART at any point before 27 weeks and those who never initiated ART (risk ratio = 1.14; 95% confidence interval: 0.84 to 1.55), but risk of extremely to very preterm birth was 2.33 (1.39 to 3.92) times as great in those who never initiated ART compared with those who did at any point before 27 weeks. Among women on ART before delivery, ART initiation before conception was associated with the lowest preterm birth risk. Conclusions: ART during pregnancy was not associated with preterm birth, and it may in fact be protective against severe adverse outcomes accompanying extremely to very preterm birth. As preconception ART initiation appears especially protective, long-term retention on ART should be a priority to minimize preterm birth in subsequent pregnancies. Abstract : Supplemental Digital Content is Available in the Text.